SILVA, Sidney de Souza (org.). Línguas em Contato: Cenários de Bilinguismo no Brasil. Coleção Linguagem e Sociedade v.2. Campinas/SP: Pontes Editores, 2011. DOI: 10.5212/MuitasVozes.v.1i2.0010 (Muitas Vozes, 2013)
.